2012
DOI: 10.1063/1.4764559
|View full text |Cite
|
Sign up to set email alerts
|

Design rules of (Mg,Zn)O-based thin-film transistors with high-κ WO3 dielectric gates

Abstract: We present a study on the design and optimization of metal-insulator-semiconductor field-effect transistors based on (Mg,Zn)O channel material with WO3 dielectric. The thickness of the dielectric and of the channel layer were adjusted independently to minimize the off-current density joff, the subthreshold slope (SS), and to modify the turn-on voltage. For optimized dielectric thickness, values of joff<10−8 A/cm2 and SS = 68 mV/decade were obtained. The variation of the (Mg,Zn)O-film thickness gives ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The 8 nm-thick IGZO TFT exhibits a relatively lower I ON , which is not reasonable. Similarly, Lorenz et al have been reported ultra-thin (8.6 nm) (Mg, Zn)O channel TFTs have a relatively lower I ON [22] . Table 1 shows the electrical parameters of IGZO TFTs with different channel thicknesses.…”
Section: Resultsmentioning
confidence: 67%
“…The 8 nm-thick IGZO TFT exhibits a relatively lower I ON , which is not reasonable. Similarly, Lorenz et al have been reported ultra-thin (8.6 nm) (Mg, Zn)O channel TFTs have a relatively lower I ON [22] . Table 1 shows the electrical parameters of IGZO TFTs with different channel thicknesses.…”
Section: Resultsmentioning
confidence: 67%
“…Compared to the MESFET, the gate current of the pn heterodiode is already dominating the drain current at an applied gate voltage of ≈0.5 V. This is due to the fact that metal‐oxide thin films tend to exhibit a porous and pitted structure when deposited by pulsed laser deposition at room temperature under a fairly high oxygen partial pressure (here 0.1 mbar). [ 26 ] The resulting formation of pinholes in the NiO layers hence remarkably enhances the probability of shunt‐induced leakage currents through the gate. Increasing the thickness of the NiO layer by approximately a factor of three to 80 nm yielded an improved and rather constant leakage current for V G < 0 V, as has been reported for ZTO‐based JFETs.…”
Section: Resultsmentioning
confidence: 99%
“…The positive shift of the threshold voltage is similar to a positive shift in the turn‐on voltage ( V on ), where V on is defined to be the gate voltage V GS corresponding to the minimum drain current I DS in the I DS versus V GS transfer characteristic of the TFTs. The calculated V on can be extracted according to the following expression: Von=Φmsd2ennormale2ϵnormaloϵnormalrkTeVnormali where Φms is work function difference between channel and gate electrode, e is the electron charge, k the Boltzmann constant, and T the temperature. ϵnormalo and ϵnormalr is the vacuum permittivity and relative permittivity of the InZnO channel, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In general, threshold voltage ( V th ) tuning can provide a convenient way to achieve expected enhancement mode (E‐mode, V th ≥ 0) devices, which is beneficial to reduced power consumption compared to the depletion mode (D‐mode, V th < 0) . As recently stated by M. Lorenz et al , the threshold voltage can be varied by the following three methods: (i) variation of the channel thickness; (ii) variation of the intrinsic electron concentration within the channel; and (iii) work function difference between the channel and the gate electrode. Among them, varying the channel layer thickness is a simple but effective method for tuning threshold voltage in TFTs .…”
Section: Introductionmentioning
confidence: 99%